Chronologische Tafel zur Geschichte des Deutschen Entomologischen Instituts 1886 - 2006. - Dathe, Holger H. (Contributions to Entomology = Beiträge zur Entomologie, 2006)
Essential events and stages of the history of German Entomological Institute are listed in chronological arrangement. Earlier reviews are actualized and critically completed. A continuation is planned using the internet-based “living review” mode [http://www.zalf.de/home_zalf/institute/dei/dei]. Keywords Deutsches Entomologisches Institut, history.